2014
DOI: 10.1038/mi.2014.1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation has an important role in the development of spontaneous colitis

Abstract: Inflammatory bowel diseases (IBD) are characterized for dysregulated intestinal inflammation. Conflicting reports have shown that activation of inflammasome could promote or decrease intestinal inflammation in an acute colitis model, whereas the involvement of inflammasome activation in chronic colitis is poorly understood. In this study, we investigated the role of inflammasome activation in the development of chronic intestinal inflammation by utilizing IL-10 knockout (KO) mouse as an animal model, which dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 50 publications
6
96
0
2
Order By: Relevance
“…This is shown in studies of mice with abnormalities of IL-10 production or signaling, where IL-10 has been shown to have a profound inhibitory effect on NLRP3 inflammasome activity; therefore, the absence of IL-10 leads to increased IL-1β production (27). In these studies, it has been shown that IL-10-KO and IL-10R-KO mice exhibit increased NLRP3 inflammasome activity and that an NLRP3 inflammasome inhibitor, such as glyburide or caspase-1 inhibitor, ameliorates colitis occurring in such mice (28,29). In addition, in related studies, it has been shown that blockade of IL-10 signaling causes colitis in TLR5-KO mice attributable to IL-1β, since it does not occur in TLR5/IL-1βR double-KO mice (30).…”
Section: Discussionmentioning
confidence: 85%
“…This is shown in studies of mice with abnormalities of IL-10 production or signaling, where IL-10 has been shown to have a profound inhibitory effect on NLRP3 inflammasome activity; therefore, the absence of IL-10 leads to increased IL-1β production (27). In these studies, it has been shown that IL-10-KO and IL-10R-KO mice exhibit increased NLRP3 inflammasome activity and that an NLRP3 inflammasome inhibitor, such as glyburide or caspase-1 inhibitor, ameliorates colitis occurring in such mice (28,29). In addition, in related studies, it has been shown that blockade of IL-10 signaling causes colitis in TLR5-KO mice attributable to IL-1β, since it does not occur in TLR5/IL-1βR double-KO mice (30).…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, a very recent report emphasizes the important role of the inflammasomecaspase-1 pathway in driving the progression of inflammation in the IL10-deficient mouse model of enterocolitis. 32 In fact, in this model, caspase-1 inhibition had a strong beneficial effect. However, the IBD mimicry of this model is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two studies found that mice lacking IL-10 have significantly elevated inflammasome activation and IL-1b production, resulting in severe colitis (37) or Ag-induced arthritis (39). However, IL-10 knockout mice also have increased production of other proinflammatory cytokines that could contribute to inflammasome activation as much as the lack of macrophage exposure to IL-10.…”
Section: Discussionmentioning
confidence: 99%